2015
DOI: 10.5530/pj.2016.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Seed oil chemical composition of Platychaete aucheri (Boiss.) Boiss

Abstract: Background: Platychaete aucheri is an endemic plant to the south of Iran and no phyochemical investigations is reported on the seeds oil. Materials and Methods: The chemical composition of Platychaete aucheri seeds oil was extracted by suxhelet apparatus, methyl esterificated and analyzed by GC and GC/MS spectroscopy method. Results: 16 compounds were determined in total and taraxasterol (19.0%), γ-sitosterol (14.1%) and lupeol (11.8%) were characterized as the most abundant components. Conclusion: Regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The sample was diluted (1% v/v) and injected with a split mode of a ratio 1: 15. Compound identification was based on mass spectral data (MS), comparing with published retention indices (RI) in NIST Mass Spectral Library, Wiley Registry of Mass Spectral Data, other published data [17][18][19][20][21][22] as well as co-chromatography with authentic samples.…”
Section: Gc/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was diluted (1% v/v) and injected with a split mode of a ratio 1: 15. Compound identification was based on mass spectral data (MS), comparing with published retention indices (RI) in NIST Mass Spectral Library, Wiley Registry of Mass Spectral Data, other published data [17][18][19][20][21][22] as well as co-chromatography with authentic samples.…”
Section: Gc/ms Analysismentioning
confidence: 99%
“…Chemical composition of B. ceiba leaves extract (BCLE) Numbering according to elution order on Rtx-5MS fused bonded column, b Percentages are the mean of three analyses. Identification was based on comparing RI: published retention indices in Wiley Registry of Mass Spectral Data (8th edition), NIST Mass Spectral Library and other published data[17][18][19][20][21][22], MS: mass spectral data and AU: co-chromatography with authentic samples. Major components were highlighted in bold.…”
mentioning
confidence: 99%
“…Fumes obtained from burning used as an adjuvant therapy to treat measles and as an agent for repelling insects. Furthermore, this plant is used as a fragrance in handmade soaps (Asgarpanah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that there are three studies refer to phytochemical investigations of the aerial part (Rustaiyan et al, 1990), seed oil components of this plant (Asgarpanah et al, 2016) and essential oil of aerial parts that demonstrated the oil has large amounts of myrtenol and borneol (Javidnia et al, 2008), both have antimicrobial activity (Tabanca et al, 2001;Aleksic & Knazevic, 2014).…”
Section: Introductionmentioning
confidence: 99%